Evaluation of Krill Meal in Commercial Diets for Juvenile Swimming Crab (Portunus trituberculatus) - Chen Guo; Min Jin; Lefei Jiao; Shichao Xie; Xiangsheng Zhang; Jiaxiang Luo; Tingting Zhu; Qicun Zhou (Aquaculture Nutrition, 2022)
An 8-week feeding trial was carried out to assess the effect of dietary krill meal on growth performance and expression of genes related to TOR pathway and antioxidation of swimming crab (Portunus trituberculatus). Four experimental diets (45% crude protein and 9% crude lipid) were formulated to obtain different replacements of fish meal (FM) with krill meal (KM); FM was replaced with KM at 0% (KM0), 10% (KM10), 20% (KM20), and 30% (KM30); fluorine concentration in diets were analyzed to be 27.16, 94.06, 153.81, and 265.30 mg kg-1, respectively. Each diet was randomly divided into 3 replicates; ten swimming crabs were stocked in each replicate (initial weight, 5.62±0.19 g). The results indicated that crabs fed with the KM10 diet had the highest final weight, percent weight gain (PWG), and specific growth rate (SGR) among all treatments (P<0.05). Crabs fed with the KM0 diet had the lowest activities of total antioxidant capacity (T-AOC), total superoxide dismutase (SOD), glutathione (GSH), and hydroxyl radical scavenging activity and had the highest concentration of malondialdehyde (MDA) in the hemolymph and the hepatopancreas (P<0.05). In the hepatopancreas, the highest content of 20:5n-3 (EPA) and the lowest content of 22:6n-3 (DHA) were shown in crabs fed with the KM30 diet among all treatments (P<0.05). With the substitution level of FM with KM gradually increasing from 0% to 30%, the color of the hepatopancreas changed from pale white to red. Expression of tor, akt, s6k1, and s6 in the hepatopancreas was significantly upregulated, while 4e-bp1, eif4e1a, eif4e2, and eif4e3 were downregulated with dietary replacement of FM with KM increasing from 0% to 30% (P<0.05). Crabs fed with the KM20 diet had notably higher expression of cat, gpx, cMnsod, and prx than those fed with the KM0 diet (P<0.05). Results demonstrated that 10% replacement of FM with KM can promote growth performance and antioxidant capacity and notably upregulate the mRNA levels of genes related to TOR pathway and antioxidant of swimming crab.